Proceedings of the 4th International Conference on Sustainable Innovation 2020-Accounting and Management (ICoSIAMS 2020) 2021
DOI: 10.2991/aer.k.210121.055
|View full text |Cite
|
Sign up to set email alerts
|

Important Points for Developing SMEs E-Commerce Towards Indonesia 4.0

Abstract: Empowering SMEs is one of the national priorities in "Making Indonesia 4.0". One way to empower SMEs towards Indonesia 4.0 is by developing an e-commerce platform for SMEs or SMEs e-commerce. Despite the large potential of SMEs in Indonesia, there are still very few of those utilizing e-commerce. Especially in the current era of globalization, SMEs need to keep up with technology to be able to compete with other businesses. Establishing SMEs' e-commerce is not easy, given that the SMEs' characteristics are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Dalam era globalisasi saat ini, UMKM perlu terus beradaptasi dengan perkembangan teknologi agar dapat bersaing dengan bisnis lainnya (Budiyanti, Permana, & Rivani, 2021). Era digital ini juga mendorong UMKM untuk memanfaatkan marketplace sebagai saluran penjualannya.…”
Section: Pendahuluanunclassified
“…Dalam era globalisasi saat ini, UMKM perlu terus beradaptasi dengan perkembangan teknologi agar dapat bersaing dengan bisnis lainnya (Budiyanti, Permana, & Rivani, 2021). Era digital ini juga mendorong UMKM untuk memanfaatkan marketplace sebagai saluran penjualannya.…”
Section: Pendahuluanunclassified
“…-E-commerce services: studies have shown [15,16] that e-commerce in MSMEs can be present in the form of applications or platforms that transition the performance of MSMEs from manual to electronic means. In this study, the e-commerce services used by MSMEs are in the form of such applications or platforms owned by the company itself or those owned by online trading service providers to help business processes and facilitate business actors, suppliers, and customers.…”
Section: Operationalizing the Study Variablesmentioning
confidence: 99%
“…E-commerce in MSMEs is defined as the utilization of ICT and applications to support business activities through the translation of such activities from a manual to an electronic context [15]. E-commerce services in MSMEs involve platforms used to increase access to technology and to encourage innovation for entrepreneurs [16]. The adoption of ecommerce services in MSMEs can have a significant influence on their performance and provides new business models and directions through innovation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is currently the country with the fourth largest growth in internet users in the world. Research conducted by Deloitte shows that digital technology (Digital Economy) can increase Indonesia's annual economic growth by 2% because it supports the growth of Small and Medium Enterprises (SMEs) (Budiyanti et al, 2021). There were 202.6 million internet users in Indonesia in January 2021.…”
Section: Optimizing Indonesia's Cyber Security and Resilience: Digiti...mentioning
confidence: 99%